Study of the Relationship betweenIntellectual Capital and Economic Performance of Saidal Complex Using VAICmodel for the period(2010-2020) - Aicha Selma Kiheli; Edward Nashaat N ashed; ZeynebTamrabet (Journal of North African Economies, 2025)
This study aims to investigate the impact of the efficiency of the components of intellectual capital of the Sidal complex on its economic performance during the period (2010-2020).Through the role played by intellectual capital with its various elements in the continuity and success of enterprises.As it distinguishes enterprises in providing information that improves the quality of accounting information provided by investors, current and prospective creditors and other stakeholders to make sound decisions. The analytical descriptive approach was used with a case study of an institution quoted on the Algiers Stock Exchange, by examining the correlation and regression relationship between the efficiency of intellectual capital and the average economic performance. The study reached a set of results, the most important of which are: we found a weak inverse correlation of working capital efficiency over average economic performance, and a strong inverse correlation between structural capital efficiency and average economic performance in the Saidal complex. There is a very poor correlation between human capital and average economic performance.